Involvement of intracellular cAMP in epirubicin-induced vascular endothelial cell injury - Takaaki Yamada; Mitsuyo Ueda; Nobuaki Egashira; Nina Zukeyama; Jun Kuwahara; Satohiro Masuda (Elsevier, 2016)
We investigated the involvement of intracellular cAMP in endothelial cell injury induced by epirubicin. Epirubicin-induced decrease in cell viability and increase in caspase-3/7 activity were reversed by a cAMP analog dibutyryl cAMP (DBcAMP) or an activator of adenylate cyclase forskolin concomitant with a phosphodiesterase inhibitor 3-isobutyl-1-methylxanthine. Moreover, epirubicin-induced elevation of lipid peroxide levels was attenuated by DBcAMP. Interestingly, the exposure of epirubicin decreased intracellular cAMP levels before the onset of epirubicin-induced production of lipid peroxidation. These results suggest that intracellular cAMP plays an important role in epirubicin-induced endothelial cell injury.